2013
DOI: 10.5713/ajas.2012.12132
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Development Is Different between Thymus from Normal and Intrauterine Growth Restricted Pig Fetus at Different Gestational Stage

Abstract: This experiment was conducted to evaluate the development of T cells in intrauterine growth retarded (IUGR) piglets at different gestational stages, and tentatively explore the relationship between T cells development and the Notch signaling pathway. A total of 18 crossbred (Landrace×Large white) primiparous sows were mated at similar weights and estruses and euthanized at d 60, 90 and 110 of gestation with six replicates for each time point. One IUGR and one normal fetus were picked from each litter. The T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In a similar model of fetal malnutrition, Badr et al reported an increased CD4:CD8 lymphocyte subpopulations ratio in adult male rats without testing the statistical significance of this observation (27) . Lin et al described an increased CD4:CD8 lymphocyte subpopulation ratio in newborn rats assessed during the gestational period; of note, the IUGR was an observational condition and not experimentally controlled (40) . This finding is also reported in a study using an ovine model of IUGR (13) .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar model of fetal malnutrition, Badr et al reported an increased CD4:CD8 lymphocyte subpopulations ratio in adult male rats without testing the statistical significance of this observation (27) . Lin et al described an increased CD4:CD8 lymphocyte subpopulation ratio in newborn rats assessed during the gestational period; of note, the IUGR was an observational condition and not experimentally controlled (40) . This finding is also reported in a study using an ovine model of IUGR (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in preclinical studies. FGR piglets present decreased T and B lymphocytes counts and proliferation in peripheral blood [ 44 ] and lower cytokine concentrations (IFN-γ, IL-4, IL-10, IL-1α, and IL-8) [ 45 ].…”
Section: Fgr Systemic Inflammation and Immunitymentioning
confidence: 99%
“…In mammals, the development and function of T cells are necessary for a successful growth, and the Notch signalling pathway, which includes Notch receptors and ligands, is fundamental to modulate T-lymphocyte development (Costa et al, 2005). Lin, Wang, Wang, Wu, and Lai (2013) found that normal foetuses had a greater proportion of T-cell subsets at earlier gestation periods than IUGR foetuses, and the Notch signalling pathway was likely partially responsible for these differences to some degree. Wang et al (2008) found that the physiology of piglets right after birth was affected by IUGR status and their intermediary metabolism was altered (cellular signalling defects, redox imbalance, reduced protein synthesis and enhanced proteolysis).…”
Section: Intr Auterine G Row Th Re S Tri C Ti On (I Ug R ) Pi G Le Tsmentioning
confidence: 94%
“…In mammals, the development and function of T cells are necessary for a successful growth, and the Notch signalling pathway, which includes Notch receptors and ligands, is fundamental to modulate T‐lymphocyte development (Costa et al., ). Lin, Wang, Wang, Wu, and Lai () found that normal foetuses had a greater proportion of T‐cell subsets at earlier gestation periods than IUGR foetuses, and the Notch signalling pathway was likely partially responsible for these differences to some degree. Wang et al.…”
Section: Intrauterine Growth Restriction (Iugr) Pigletsmentioning
confidence: 99%